2012
DOI: 10.5070/v425110398
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Prevalence of Cryptosporidium spp. and Giardia spp. from Wild Rodents Adjacent to Produce Production Fields in California

Abstract: Between 2009 and 2011, fecal samples were collected from ten species of wild rodents in locations adjacent to leafy green blocks in a major produce production region of California. Samples were screened for Cryptosporidium spp. oocysts and Giardia spp. cysts using immunofluorescent microscopy. Five and seven species of wild rodents carried Cryptosporidium spp. and Giardia spp., respectively. In general, 26.0% and 24.2% of the trapped wild rodents were positive for Cryptosporidium spp. and Giardia spp., respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…The relative importance of wild animals in the contamination of plants is uncertain, but Li et al (2013) found 26.0and 24.2% of wild rodents trapped next to produce fields in California were positive for Cryptosporidium spp. and Giardia spp., respectively [92]. Feral swine from the same produce growing region were also shown to harbour these parasites [93].…”
Section: Parasitesmentioning
confidence: 98%
“…The relative importance of wild animals in the contamination of plants is uncertain, but Li et al (2013) found 26.0and 24.2% of wild rodents trapped next to produce fields in California were positive for Cryptosporidium spp. and Giardia spp., respectively [92]. Feral swine from the same produce growing region were also shown to harbour these parasites [93].…”
Section: Parasitesmentioning
confidence: 98%
“…Also, new guidelines for researchers working with wild rodents have been published (Kelt et al 2010). Finally, it is worth noting that rodents have been implicated in food safety issues, as they can contribute to field crop contamination with E. coli and other disease pathogens (Salmon 2008, Li et al 2012. Another human safety issue is the attraction of birds to airports to feed on rodents (mainly deer mice and voles), resulting in increased risk of bird-aircraft strikes (Witmer and Fantinato 2003).…”
Section: Disease Pathogensmentioning
confidence: 99%